1988
DOI: 10.1210/jcem-67-6-1258
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Prednisone of Growth Hormone (GH) Response to GH-Releasing Hormone in Normal Men

Abstract: Glucocorticoids increase GHRH-stimulated GH secretion when added in vitro to cultured monkey, rat, and human pituitary cells and when injected in vivo into anesthetized rats. Yet, in man glucocorticoids inhibit linear growth and GH secretion. To clarify this apparent disparity and to determine if glucocorticoid stimulation can augment GH release in man after direct pituitary stimulation with GHRH, we administered 1 microgram/kg GHRH dosage to seven normal men before and after a 4-day course of prednisone (20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Carbohydrate metabolism can also be affected by prolonged steroid administration, causing insulin resistance to both hepatic and peripheral tissues, leading at times to frank carbohydrate intolerance [9]. When administered to growing children these side effects of GC treatment are compounded further by a potent and significant suppression of linear growth [10, 11, 12, 13]. Hence, the prevention or amelioration of some of these adverse events associated with chronic GC use could have important implications on the management of a wide variety of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate metabolism can also be affected by prolonged steroid administration, causing insulin resistance to both hepatic and peripheral tissues, leading at times to frank carbohydrate intolerance [9]. When administered to growing children these side effects of GC treatment are compounded further by a potent and significant suppression of linear growth [10, 11, 12, 13]. Hence, the prevention or amelioration of some of these adverse events associated with chronic GC use could have important implications on the management of a wide variety of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In humans administration of glucocorticoid has been shown to increase endogenous GH secretion [12, 14, 16, 26]whereas the effect of glucocorticoid administration on GH release during GH stimulation test are ambiguous as both blunted and enhanced responses have been reported [5, 6, 7]. During glucocorticoid exposure increased levels of IGF-I has frequently been described [1, 2, 5, 8, 11, 12, 13, 14, 15, 16], although some studies found no changes [9, 10, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid administration in healthy adults has been shown to increase protein oxidation, which is prevented by co-administration of GH [1, 2, 3, 4]. The effects of hypercortisolaemia on GH release are, however, ambiguous as both blunted and enhanced responses to GH stimulation tests have been reported [5, 6, 7]. Moreover, serum total IGF-I concentrations are normal or even elevated after both short-term and more prolonged exposure to glucocorticoids [1, 2, 5, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of linear growth inhibition by GC has not been defined. The findings regarding the effects of GC on GH secretion are controversial [4, 5, 6, 7, 8]. It appears that GC may affect not so much the level of GH secretion, but rather the nyctohemeral GH secretion profile, resulting in delayed and attenuated nocturnal GH secretion peaks [9].…”
Section: Discussionmentioning
confidence: 99%